2003
DOI: 10.1053/rmed.2003.1483
|View full text |Cite
|
Sign up to set email alerts
|

Addition of salmeterol to fluticasone propionate treatment in moderate-to-severe asthma

Abstract: This study was designed to determine whether the benefit of adding salmeterol was superior to doubling the dose of fluticasone propionate (FP) over 6 months, compared to a control group who remained on a lower dose of FP. The multi-centre, double-blind, parallel group study involved 496 symptomatic asthmatic patients with a history of exacerbations on 500-800 micrograms (microg) inhaled corticosteroids (ICS) twice daily (b.d.) in a broadly representative group of 100 hospitals and general practices in six coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 16 publications
2
31
0
4
Order By: Relevance
“…However, data from the SMART study (a large multicenter trial examining safety of salmeterol) (3) and the current findings suggest that differential response to LABAs in African Americans exist. Indeed, despite the fact that multiple studies of similar and smaller size in predominantly white populations had demonstrated superiority of added salmeterol in exacerbations, symptom control, and medication use (19)(20)(21), the only prospective asthma study in African Americans to date (salmeterol or ICS vs. ICS alone in 475 African Americans) (22) revealed a blunted response to LABA in African Americans. That study failed to demonstrate that exacerbations were decreased or that asthma control (except night-time awakenings) was improved by the addition of salmeterol.…”
Section: Discussionmentioning
confidence: 99%
“…However, data from the SMART study (a large multicenter trial examining safety of salmeterol) (3) and the current findings suggest that differential response to LABAs in African Americans exist. Indeed, despite the fact that multiple studies of similar and smaller size in predominantly white populations had demonstrated superiority of added salmeterol in exacerbations, symptom control, and medication use (19)(20)(21), the only prospective asthma study in African Americans to date (salmeterol or ICS vs. ICS alone in 475 African Americans) (22) revealed a blunted response to LABA in African Americans. That study failed to demonstrate that exacerbations were decreased or that asthma control (except night-time awakenings) was improved by the addition of salmeterol.…”
Section: Discussionmentioning
confidence: 99%
“…4) [18]. This provides additional evidence that a treatment regimen involving an increase of the maintenance ICS dose alone has limited additional benefit in improving symptom control in most patients [7,15,[31][32][33][34]. Such a regimen may result in overtreatment with ICS, potentially increasing the risk of long-term side-effects [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically relevant exacerbations and as-needed medication use were the key effectiveness measures, as often used in clinical practice. In addition, patients were not excluded from the study based on reversibility criteria as in standard efficacy trials of LABA therapy [7,13,15], a factor potentially reducing the applicability of clinical trial findings to routine clinical practice [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews have found a 12-14% reduction in the risk of an exacerbation with traditional ICS/LABA maintenance therapy plus SABA for relief compared with a higher ICS dose plus SABA in patients with moderate to severe asthma (17,18). However, the value of increasing ICS dose for improving daily asthma control may be limited (19).…”
Section: The Role Of Ics and Laba In Improving Asthma Controlmentioning
confidence: 99%